Correction: Predicting the risk of atherosclerotic cardiovascular disease among adults living with HIV/AIDS in Addis Ababa, Ethiopia: A hospital-based study. - PLOS One Editors (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0260109.].